Analytical exact solution of telegraph equation using HPM - Ahmad, Jamshad; Mohiuddin, Ghulam (BIBECHANA, 2016)
In this paper, exact solutions of different variants of second order hyperbolic telegraph equation are investigated with Homotopy Perturbation Method (HPM). The results determined by the proposed method are quite satisfactory and shows that HPM technique is very effective and useful for solving the nonlinear partial differential equations (PDEs) with given initial or boundary conditions. The proposed iterative scheme finds the solution without any discretization, linearization or restrictive assumptions.BIBECHANA 14 (2017) 30-36